Treatment for COVID-19—a cohort study from Northern Italy - Guglielmetti, Lorenzo; Aschieri, Daniela; Kontsevaya, Irina; Calabrese, Francesco; Donisi, Alessandra; Faggi, Alberto; Ferrante, Patrizia; Fronti, Elisa; Gerna, Laura; Leoni, Maria Cristina; Paolillo, Franco; Ratti, Giovanna; et al. (Scientific reports, 2021)
Multicentre, retrospective cohort study with multivariable Cox proportional-hazards modelling and survival-time inverse-probability-weighting, evaluating the impact of different treatments on survival of proven COVID-19 patients admitted to two Hospitals in the province of Piacenza, Italy. Use of tocilizumab and of high doses of low molecular weight heparin, but not of antivirals (either alone or in combination), azithromycin, and any corticosteroid, was independently associated with lower mortality. Our results support further clinical evaluation of high doses of low molecular weight heparin and tocilizumab as COVID-19 therapeutics.